The Allocation of Risk: Some Implications of Fixed Versus Index-Linked Mortgages - Baesel, Jerome B.; Biger, Nahum (Journal of Financial and Quantitative Analysis, 1980)
Jerome B. Baesel, Nahum Biger, The Allocation of Risk: Some Implications of Fixed Versus Index-Linked Mortgages, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 2 (Jun., 1980), pp. 457-468